Factitious Disorder (Munchausen Syndrome) in Plastic Surgery: A Systematic Review of 42 Cases. Issue 4 (April 2021) - Evans, Rhian Louise; Tew, Jennifer Catherine; Yates, Gregory Peter; Feldman, Marc
Abstract : Introduction: Patients with factitious disorder (FD) or "Munchausen syndrome" intentionally fabricate or induce medical problems for psychological gratification. They may deceive plastic surgeons into performing multiple unnecessary procedures. We undertook the first systematic review of FD case reports in plastic surgery. Our aims were 2-fold: (1) describe the adverse outcomes associated with these cases and (2) identify strategies for their prevention by surgeons. Methods: MEDLINE, EMBASE, and SCOPUS databases were searched. We included cases in which an adult with FD presented to a plastic surgeon. Our search returned a total of 42 eligible cases reported from North America (43%), Europe (37%), and Asia (20%). Results: Seventy-six percent of patients were women, and 62% worked in health care. Sixty percent had a comorbid psychiatric disorder, the most common (50%) being depression. Ninety-three percent of our sample presented with self-induced lesions. The average delay in diagnosis of FD was 54 months, with 46% of patients receiving multiple surgical procedures in this time, including debridement (36%) and skin grafts (39%). Surgical wounds were frequently exploited by patients to remain in, or return to, hospital: 50% contaminated or manipulated their wounds to prevent healing. Thirty-six percent of cases resulted in significant long-term disability (24%) or disfigurement (12%). Ten percent of patients received an amputation. Outcomes were improved when patients were confronted by surgeons, however, and 62% were willing to see a psychiatrist. Surgeons were able to support recovery in 33% of cases—for example, by using occlusive wound dressings. Conclusions: Patients with FD who present to plastic surgeons are high risk: the majority require surgical intervention for severe self-injury, and many engage in harmful behaviors, such as "doctor-shopping." Early recognition of FD in plastic surgery is, therefore, crucial and may be achieved via careful examination of lesions for unusual morphology. Medical records may reveal extensive health care service use and negative investigations. Finally, plastic surgeons may play an important role in managing such patients. Management strategies include direct observation by nursing staff in the postoperative period and use of strict occlusive dressings to prevent access to surgical wounds. Abstract : Supplemental digital content is available in the text.